Behavior, Attitudes, and Eating and Nutritional Practices in Pregnant Women. Pamplona Alta, Red Sjm-Vmt. disa ii. Lima-South, Peru - Clara Gilma (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Low food consumption, anemia, and frequent infections during pregnancy are causes of maternal malnutrition; For this reason, it is important to know attitudes and practices during pregnancy to design messages in favor of the nutrition of the pregnant woman. Objective.- To have a basic line of knowledge, attitudes and practices of pregnant women in Ollantay (poor suburban area) that will allow us to carry out educational interventions. Method.- 156 surveys were applied, divided into 6 axes: (i) general data, (ii) knowledge about nutrition; (iii) nutritional attitudes; (iv) nutritional practices; (v) other foods; (vi) habits. Results.- The study was carried out in 2006. 86% know that they should drink milk, however only 35% take it every day; 33%, two or three times a week and 27%, sometimes. 85% know that they should take ferrous sulfate; 91% who must consume 3 main meals and 1 snack. 59% know which foods facilitate the absorption of iron and 47% which are rich in iron. Egg: 44% consume it sometimes, 38% two or three times a week and 13% every day. 58% consume roast chicken, 30% hamburger, 79% ice cream, 56% cakes and sweets, 66% soft drinks. Conclusions.- Pregnant women know how many meals a day they should consume. Half know which foods are rich in iron and which facilitate its absorption. Foods rich in iron are not to his liking. A high percentage have bad eating habits. Protein-rich foods are rarely consumed by pregnant women.